There was a King in Egypt - Lorimer, Norma, 1864-1948 (Salt Lake City, UT : Project Gutenberg, 2007)
"There Was a King in Egypt" by Norma Lorimer is a historical novel written in the late 1910s. The story centers around Michael Amory, a young English Egyptologist, as he engages in excavations related to the tomb of Akhnaton's mother, amidst the backdrop of ancient Egyptian culture and early 20th-century explorations. The narrative blends history with themes of mysticism and romantic entanglements, particularly involving Michael, his colleague Freddy Lampton, and Freddy's sister, Margaret, who arrives in the excavation camp. The beginning of the novel introduces Michael Amory against the serene yet daunting landscape of Egypt at dawn, depicting his fascination with the ancient ruins and hinting at the spiritual connection he feels with the land. He is soon disrupted by thoughts of life beyond his archaeological pursuits, particularly with the impending arrival of Margaret, which stirs a mix of anticipation and annoyance in him. The narrative immerses the reader in the excavation process, highlighting the daily realities the characters face and setting the stage for the complex interplay of relationships and historical reverence that will unfold as Margaret joins the expedition and Michael grapples with his feelings for her and the echoes of Akhnaton's legacy. (This is an automatically generated summary.)
Release date is 2007-12-26
E-text prepared by Al Haines
Keywords: Egyptologists -- Fiction; Excavations (Archaeology) -- Egypt -- Fiction